Pengaruh E-Flashcard pada Pengetahuan dan Sikap Remaja terkait Perilaku Seksual Berisiko - Maharani, Tiari Dhiya; Sriwenda, Djudju; Mulyati, Sri Wisnu; Fajrin, Anita Megawati (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2025)
Background: Adolescence is a period marked by emotional instability, especially regarding sexual behavior. Curiosity about adult activities, such as sexual intercourse, often arises, and a lack of sexual education is a major factor contributing to risky sexual behavior. Educational tools such as e-flashcards, which provide materials and questions about sexual health, can be used to improve adolescent knowledge and attitudes. Method: This study applied a quantitative approach with a quasi-experimental design using a non-equivalent control group. The experimental group was students from SMA Negeri Jatinangor, while the control group was from SMA Negeri 1 Majalaya. A total of 112 participants were selected using cluster random sampling. The instrument was a questionnaire adapted from Nadya (2022). Data were analyzed using the Mann-Whitney U Test. Findings: Findings revealed that e-flashcards significantly improved knowledge. The Mann-Whitney test showed a mean rank difference of 17.42 with p = 0.003 (p < 0.05). For attitudes, the mean rank difference was 16.66 with p = 0.006 (p < 0.05). Although both groups improved, e-flashcards were more effective than PowerPoint. Implication: E-flashcards effectively enhance adolescents’ knowledge and attitudes on risky sexual behaviors. Schools are encouraged to integrate this medium into health education programs